Pengaruh Faktor Fundamental Dan Risiko Sistematis Terhadap Return Saham Syariah - Dwi Budi Prasetyo Supadi; M. Nuryatno Amin (Media Riset Akuntansi, Auditing & Informasi, 2012)
The research was conducted to examine the influence of fundamental factors and systematic risk to Islamic stocks Return. Fundamental factor in this study is proxied by: (1) Earnings per Share (EPS), (2) Return on Equity (ROE), and (3) Debt to Equity Ratio (DER), whereas systematic risk is proxied by Stocks of Beta.The population of this study is all companies listed on the Indonesia Stock Exchange (IDX) incorporated in the Jakarta Islamic Index (JII). Observation period in the study conducted from 2008 to 2011. Of this population, the selection of the sample using purposive sampling criteria: (1) The Company is always consistent on the Jakarta Islamic Index (JII) at least 4 times of the publication period December 2008 to December 2011, (2) The Company perform Initial Public Offering (IPO) in 2007, (3) Issuing an audited financial statements in the period 2008 to 2011, and (4) Getting a profit during the period of 2008to 2011. With these criteria, the sample obtained by 20 companies. Performed during the study period of 4 (four) years and analytical methods using linear regression analysis.The results of this study indicate that the Earning per Share (EPS), Return on Equity (ROE), and Stocks of Beta positive, but not significant to Islamic stocks Return, while the Debt to Equity Ratio (DER) negative, but not significant effect on Islamic stocks Return. Simultaneously Earning per Share (EPS), Return on Equity (ROE), Debt to Equity Ratio (DER), and Stocks of Beta have no effect on Islamic stocks Return.Keywords: Fundamental Factors, Earning per Share, Return on Equity, Debt to EquityRatio, Systematic Risk, Stocks of Beta and Islamic stocks Return.